2016
DOI: 10.7567/apex.9.052102
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced light extraction in tunnel junction-enabled top emitting UV LEDs

Abstract: Abstract:The efficiency of ultra violet LEDs is critically limited by the absorption losses in ptype and metal layers. In this work, surface roughening based light extraction structures are combined with tunneling-based top-contacts to realize highly efficient top-side light extraction efficiency in UV LEDs. Surface roughening of the top n-type AlGaN contact layer is demonstrated using self-assembled Ni nano-clusters as etch mask. The top surface roughened LEDs were found to enhance external quantum efficiency… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…[10][11][12] Since the structure is terminated with an n-AlGaN layer, which has low spreading resistance, the top metal electrode coverage can be minimized to allow light extraction from the top surface. 13 Besides, aluminum, as the only UV reflective metal with a high reflectivity above 90% in the deep UV range, can be used to form n-type reflective top contact. [14][15][16] This provides flexibilities in the development of optimized light extraction schemes based on the tunnel-injected UV LED structure.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12] Since the structure is terminated with an n-AlGaN layer, which has low spreading resistance, the top metal electrode coverage can be minimized to allow light extraction from the top surface. 13 Besides, aluminum, as the only UV reflective metal with a high reflectivity above 90% in the deep UV range, can be used to form n-type reflective top contact. [14][15][16] This provides flexibilities in the development of optimized light extraction schemes based on the tunnel-injected UV LED structure.…”
mentioning
confidence: 99%
“…9 Tunneling hole injection into p-AlGaN was demonstrated with appreciable light emission in a wide UV wavelength range of 325-257 nm from the tunnel-injected UV LED structure. 9,13,[16][17][18]31 Incorporation of tunnel junctions into nanowire LEDs has also been reported with excellent device performances. 32,33 In this work, we demonstrate efficient deep UV LEDs with an on-wafer peak external quantum a)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on some recent simulation and experimental work, 8 periods of the active region seem to be the optimum in terms of the light output and forward voltage drop across the device. Reducing the number of periods and further improvements in the p-layer design using tunnel-contacts 26,27 can potentially help improve the hole injection problem for deep-UV LEDs. Fig.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17] Nevertheless, the external quantum efficiencies (g EQE ) of AlGaN-based UV LEDs still remain less than 10% for wavelength (k) < 300 nm till recently. [4][5][6][7][8][9] This extremely low g EQE can mainly be attributed to the material challenges including high dislocation densities (10 10 cm À2 in AlN and AlGaN layers) 10,11 and relatively low electrical conductivity in p-and n-type AlGaN cladding layers, [12][13][14][15][16][17] as well as the physics challenges such as a severe valence band-mixing effect in conventional AlGaN QW structures. [18][19][20][21][22] Specifically, previous studies revealed that the crystalfield split-off (CH) subband is dominant in the valence band for high Al-content (>68%) AlGaN QWs, which results in dominant transverse-magnetic (TM)-polarized emission at k $ 220-230 nm.…”
mentioning
confidence: 99%